A tool to assess fitness among adults in public health studies - Predictive validity of the FFB-Mot questionnaire - Alexander Woll; Laura Cleven; Darko Jekauc; Janina Krell-Roesch; Klaus Bös (BMC, 2023)
Abstract Background Fitness has important implications for physical activity behavior and is associated with various health-related outcomes. It can be assessed through a test battery or a self-reported questionnaire. One example is the FFB-Mot (Funktionsfragebogen Motorik; engl. functional fitness questionnaire) which consist of 28 items to assess four components of fitness in adults: cardiorespiratory fitness/ endurance, muscular strength, gross motor coordination, and flexibility. The aims of this manuscript were to (1) provide an English-version of the FFB-Mot questionnaire (developed from the German-version using translation and back-translation) to the international community of researchers in the areas of physical activity, fitness and health in adults, and (2) examine the predictive validity of the FFB-Mot questionnaire in a large sample of community-dwelling adults. Methods We used data from a longitudinal study in Germany with four measurement waves over a period of 18 years, with samples ranging between 310 and 437 participants (1572 adults in total, mean ages 46-58 years). To assess predictive validity, we calculated Pearson correlations between FFB-Mot data collected in 1997 and external health-related criteria (i.e., subjective health status, physician-rated health status, back pain, physical complaints and physical activity in minutes per week) collected in 2002, 2010, and 2015, and separately for males and females. Results We observed correlations between higher FFB-Mot scores with better subjective health status (in 2002: males, r = 0.25; females, r = 0.18; in 2010: males, r = 0.29; females, r = 0.28; in 2015: males, r = 0.40), and higher physical activity (in 2002: males, r = 0.24; females, r = 0.25; in 2010: males, r = 0.30; females, r = 0.38; in 2015: females, r = 0.27). Higher FFB-Mot scores were also correlated with lower back pain (in 2002: males, r = -0.23; females, r = -0.25; in 2010: females, r = -0.22), less physical complaints (in 2002: males, r = -0.36; females, r = -0.24), and better physician-rated health status (in 2002: males, r = -0.41; females, r = -0.29, 2010: males, r = -0.38; females, r = -0.44; in 2015: males, r = -0.47). Conclusions Our results suggest that the FFB-Mot to assess fitness in adults has predictive validity for health-related outcomes as indicated by significant correlations, albeit some effect sizes are small. The FFB-Mot may be used as one-time assessment of self-reported fitness, or for repeated testing to assess change of self-reported fitness over time and in different settings (e.g., public health research).